(untitled) (Gestão & Regionalidade, 2024)
The goal was to estimate the impact of Micro and Small Enterprises (MSE), opting for the Simple National Tax Regime (SNT), on the Service Tax (ISS) collection and employment in the municipalities of the Metropolitan Region of the State of Rio de Janeiro (MRSRJ). A panel data method was used for the data from 2010 to 2019. The results showed a significant growth in the number of SNT companies in the MRSRJ municipalities and a positive correlation between the number of SNT companies and the ISS collection of the MRSRJ municipalities. However, a low positive correlation was noted between these companies and the formal jobs they generated. It was concluded that the growth in the number of companies opting for the Simple National is different from the growth of jobs generated by these companies, demonstrating that the role of the Simple National in the formalization of small businesses is greater than its role in job creation.